Biological Deacidification of Musts Induced by Yeasts or Malolactic Bacteria and the Effect on Wine Quality - van Rooyen, T.J.; Tracel, R.P. (South African Journal of Enology and Viticulture, 2017)
This study investigated the possible use of Schizosaccharomyces pombe and Schizosaccharomyces malidevorans for deacidification of red wines during alcoholic fermentation, in comparison with existing deacidification practices of induced or spontaneous malolactic fermentation (MLF) in South Africa. In red must, the effect of these yeasts on alcoholic fermentation rate, rate of L-malic acid removal, as well as the effect of mixed cultures with Saccharomyces cerevisiae at different inoculum concentrations and sizes of inocula on wine quality was investigated. In white must, the effect of pure culture inocula and temperature on wine quality and production of volatile bouquet substances was also studied. Both Schizosaccharomyces spp. were found to deacidify normal concentrations of L-malic acid in musts effectively at higher growth temperatures, but the ability of Schiz. pombe was inhibited by high concentrations of Lmalic acid which was not pH dependent. Certain key volatile fermentation bouquet compounds were produced in very low quantities, which seems to be the reason for poor sensory quality wines produced by Schizosaccharomyces.